PEMBUATAN MARKETPLACE DENGAN FITUR SISTEM PENUNJANG KEPUTUSAN UNTUK MENENTUKAN KAYU TENIS MEJA YANG SESUAI DENGAN GAYA PERMAINAN MENGGUNAKAN METODE SMART BERBASIS WEB - James Suryapranata; Desi Arisandi; Manatap Dolok Lauro (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
Table tennis is a very popular sport in the world, including Indonesia. Table tennis Sports in Indonesia is headed by the All-Indonesia Table Tennis Association (PTMSI). In addition, Indonesia also has the largest table tennis community, Table Tennis Mania, consisting of 25,000 members who are active in social media Facebook. The purpose of making this application is to help the experienced table tennis players to choose the appropriate table tennis blade using the decision support system the SMART method. This Method allows the system to calculate player`s playing frequency with the blade`s spesification resulting the best recommendation for the player. Also this website can be used by the players of table tennis or table tennis sellers to do the sale of table tennis blade through the marketplace. This website has been tested by several people in various table Tennis Union (PTM) in Jakarta and produce positive feedback.